Virtual Quality Control in Middle Ear Surgery: Is Image-guided Tympanoscopy a Valuable Tool for Depicting Borderline Situations?. Issue 7 (August 2020) - Jakob, Till F.; Zaoui, Karim; Kromeier, Jan; Baumann, Tobias; Becker, Christoph; Lasurashvili, Nikoloz; Neudert, Marcus; Beleites, Thomas; Offergeld, Christian
Abstract : Hypothesis: Before modern imaging was introduced, revision surgery was the only way to evaluate possible reasons for inadequate improvement in hearing after ossicular replacement during reconstructive middle ear surgery. Background: The aim of this study was to evaluate freely navigable virtual tympanoscopy using different computed tomographic modalities. We compared cone-beam computed tomography (CBCT), flat panel computed tomography (FPCT), and conventional computed tomography in helical mode (CTH), volume mode (CTV), and ultra high resolution mode (CTD). Methods: Four temporal bone specimens were reconstructed with partial or total ossicular replacement prostheses. The best functional results for prosthetic coupling were achieved under the control of laser Doppler vibrometry (LDV). Afterward, a progressive step-by-step decoupling of the prostheses was carried out. Different prosthesis positions were evaluated by LDV as well as different computed tomographic modalities with 3D reconstruction of each dataset. Results: Anatomical structures were better depicted and the best position and coupling of inserted prostheses were achieved using CBCT. All imaging techniques could be used to control the position of middle ear prostheses, but CBCT provided the highest resolution and the best image quality in both 2D and 3D reformations and in 3D-animated video representation. Conclusion: Compared with several other imaging modalities, CBCT was best at depicting miscellaneous coupling problems. Noninvasive detection of coupling problems caused by minimal loss of contact between prostheses and middle ear ossicles will influence the clinical outcome. This early detection will help to determine whether revision surgery is needed. Abstract : Supplemental Digital Content is available in the text